2011
DOI: 10.1134/s1070428011080057
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular electrophilic cyclization of functional derivatives of unsaturated Compounds: I. Synthesis of 5-arylsulfanyl-6-phenylpiperidin-2-ones from cinnamylacetamides and arylsulfenyl chlorides

Abstract: Sterically nonhindered N-alkyl(aryl)amides of cinnamylacetic acid in the reaction with phenyl(4-tolyl)sulfenyl chlorides in acetic acid in the presence of lithium perchlorate undergo a selective cyclization into 5-arylsulfanyl-6-phenylpiperidin-2-ones. Under similar conditions the reaction with arylsulfenyl chlorides of amides containing bulky substituents at the nitrogen atom resulted in 5-arylsulfanyl-6-phenyltetrahydropyran-2-iminium perchlorates, which by treatment with aqueous ethanol were converted into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…With Mn(I)‐catalyzed hydroalkenylation of unsaturated amides, we can readily assemble a rich library of structurally diverse β‐alkenylated amides. As shown in Scheme , several multisubstituted five‐ and six‐membered lactams can be prepared in one step and in moderate to good yields, further stressing the synthetic value of the reaction in organic synthesis and drug discovery …”
Section: Methodsmentioning
confidence: 99%
“…With Mn(I)‐catalyzed hydroalkenylation of unsaturated amides, we can readily assemble a rich library of structurally diverse β‐alkenylated amides. As shown in Scheme , several multisubstituted five‐ and six‐membered lactams can be prepared in one step and in moderate to good yields, further stressing the synthetic value of the reaction in organic synthesis and drug discovery …”
Section: Methodsmentioning
confidence: 99%
“…As shown in Scheme 6, several multisubstituted five-and six-membered lactams can be prepared in one step and in moderate to good yields, further stressing the synthetic value of the reaction in organic synthesis and drug discovery. [41][42][43] We found that the addition of 3 equivalents of EtOH can improve the yield of this reaction, and we postulated that it may play a special role as a proton source in the protodemetalation. As shown in Scheme 7 a, deuterium-labeling control experiments indicated that the hydrogen atom at the a- 8) at 120 8C, and these will immediately undergo transmetallation with aryl boronic acids in the presence of external base to generate an intermediate (9).…”
Section: Angewandte Chemiementioning
confidence: 84%
“…Не-щодавно [4] на основі реакції електрофільної внут-рішньомолекулярної циклізації N-алкіл(арил)амі-дів цинамілоцтової кислоти з арилсульфенілхло-ридами ми розробили ефективний стереоселек-тивний метод синтезу раніше невідомих 5-арил-сульфаніл-6-фенілпіперидин-2-онів. Ці сполуки містять чутливі до дії відновників карбонільну та сульфанільну групи (остання також схильна до окиснення) і є зручними моделями для дослі-дження селективності перебігу таких перетво-рень.…”
Section: селективное восстановление и окисление 1-арил-5-арилсульфаниunclassified